Perceptions of Primary and Secondary Education Students in Kendari City towards Youtube - Muhammad Arsyad (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
The purpose of this research is to find out students' perceptions of digital media YouTube in primary and secondary level students in the city of Kendari. This study uses a qualitative descriptive method with interview, observation, and documentation techniques. Data were analyzed using descriptive statistics. The results of the study show the perceptions of elementary and secondary level students understand Youtube media. Elementary and secondary level students, on average, understand the Youtube application with the highest Percentage on the SD/MI level at 58.33%, SMP/MTS at 66.67%, and SMA/MA/SMK who understand and fully understand at 88.89%. On Youtube features, elementary to secondary level students understand 36.11%, 41.67%, and 44.45%, respectively. For the benefits of the Youtube application, elementary to secondary level students understand, and the data obtained are 38.89%, 52.77%, and 55.55%, respectively, with the rest of the participants already fully understanding. In addition, students understood the Youtuber profession and obtained data from 33.33%, 50%, and 61.11%, respectively. Also, students also understand the dangers or negative impacts of using Youtube, with successive data of 30.55%, 69.45%, and 77.79%. Overall can, it is said that students at the final secondary level, namely SMA/MA/SMK, understand more about the Youtube application, its features, benefits, the Youtuber profession, and the dangers of Youtube compared to junior high school students, namely SMP/MTS and the elementary level of SD/MI.